Applying John Holland’s Career Theory to Students' Career Choice - Chaterina Yeni Susilaningsih (Journal of Education and Teaching Learning, 2026)
This study aims to determine whether John Holland's career theory is effective and how John Holland's career theory is applied to students' career choices. The research method used is descriptive quantitative involving 76 students of class XII E and XII G at SMA Negeri 6 Madiun as research samples, using purposive random sampling technique with consideration based on suggestions from BK (Guidance and Counseling) teachers to be more focused in providing follow-up. Data were collected through questionnaires and observations. The data collection method was carried out by administering Riasec tests and career choice questionnaires. The questionnaire instrument (career choice scale) used the Likert model. The analysis technique used statistical analysis with the t-test formula, to test the hypothesis whether John Holland's theory is effective in students' career choices. The results of the study showed a difference in the t-test calculation before and after being given John Holland's career test theory with a t-value of 6.408. The probability value of 0.000 <0.05, so it can be stated that H0 is rejected and Ha is accepted, which means that the application of John Holland's career theory is effective in students' career choices.